PSYCHOSOCIAL DEVELOPMENT THROUGH TRADITIONAL GAMES AND SPORTS IN ELEMENTARY SCHOOL STUDENTS - Julianti, Rekha Ratri; Suherman, Adang; Ma'mun, Amung; Budiana, Dian; Zinat Ahmad, Irfan; Purwanto, Setyo (STKIP Muhammadiyah Kuningan, 2024)
The purpose of this study was to determine the formation of psychosocial through traditional games and sports. Various traditional games and sports activities such as clogs, boy-boyan, cat-mouse, hopscotch, gobak sodor, snakes and ladders and stilts can create things that arouse students' social attitudes. This creates a learning experience to be able to train teamwork, goal setting, psychosocial adjustment needs and psychosocial adjustment needs from social relationships. This study used an experimental method with a pretest and posttest design with a sample of 25 elementary school students. The results showed that there was a significant influence on increasing psychosocial in the sample given the traditional games and sports program.